Theoretical bases of the competition and competitiveness in the market environment (Путеводитель предпринимателя, 2020)
In the conditions of universal globalization and integration of developing economy into economy of more developed countries, special value the competitive environment taking into account differentiation gets it the weakest and strengths. About theoretical judgment of a role and value of the competition, competitiveness of managing subjects speech in this publication also will go.